2008
DOI: 10.1186/1752-4458-2-13
|View full text |Cite
|
Sign up to set email alerts
|

Hope, despair and transformation: Climate change and the promotion of mental health and wellbeing

Abstract: Background This article aims to provide an introduction to emerging evidence and debate about the relationship between climate change and mental health. Discussion and Conclusion The authors argue that: i) the direct impacts of climate change such as extreme weather events will have significant mental health implications; ii) climate change is already impacting on the social, economic and environmental determinants of mental health with the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
325
1
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 450 publications
(339 citation statements)
references
References 29 publications
(33 reference statements)
4
325
1
9
Order By: Relevance
“…This included a perceived sense of depression throughout the community because of decreased access to the land resulting from hazardous ice conditions, accompanied by a sense of isolation in not being able to travel. These Elder and senior perspectives support communitywide observations previously reported in the literature (Berry, Bowen, & Kjellstrom, 2010;Cunsolo Willox et al, 2012, 2013a,b, 2014Fritze et al, 2008;Saniotis & Irvine, 2010). Furthermore, this research identified Elder-specific concerns and worries about how climate change might affect future health challenges for Inuit youth, including a loss of Inuit language and culture.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This included a perceived sense of depression throughout the community because of decreased access to the land resulting from hazardous ice conditions, accompanied by a sense of isolation in not being able to travel. These Elder and senior perspectives support communitywide observations previously reported in the literature (Berry, Bowen, & Kjellstrom, 2010;Cunsolo Willox et al, 2012, 2013a,b, 2014Fritze et al, 2008;Saniotis & Irvine, 2010). Furthermore, this research identified Elder-specific concerns and worries about how climate change might affect future health challenges for Inuit youth, including a loss of Inuit language and culture.…”
Section: Discussionsupporting
confidence: 73%
“…Human-induced global climate change is now acknowledged as reality within the scientific community (Christensen et al, 2007;Füssel, 2009). Projected increases in regional temperatures-combined with changes in the intensity, duration, and frequency of precipitation and severe storms-are expected to have substantial impacts on physical, mental, and emotional health outcomes, resulting from increased exposure to infectious disease, water and food insecurity, population displacement, conflicts over natural resources, and degradation of landscapes and ecosystems (Christensen et al, 2007;Costello et al, 2009;Fritze, Blashki, Burke, & Wiseman, 2008;Frumkin, Hess, Luber, Malilay, & McGeehin, 2008;Swim et al, 2011). Given physical activity levels and poorer nutrition; impacts on mental and emotional health, including feelings of isolation and depression; and an identified need for community-wide adaptation.…”
mentioning
confidence: 99%
“…Extreme weather events and environmental stressors associated with global climate change are likely to have immediate effects on the prevalence and severity of mental health issues in affected communities, significant implications for mental health services, and ongoing disruptions to the social, economic and environmental determinants that promote mental health in general (Costello et al, 2009;Few, 2007;Fritze et al, 2008;Page & Howard, 2010). For example, impacts of natural disasters include acute and posttraumatic stress disorder (Galea, Nandi, & Vlahov, 2005); somatic disorders (van den Berg, Grievink, Yzermans, & Lebret, 2005); major depression (Marshall et al, 2007); and other problems such as drug and alcohol abuse, higher rates of suicide, and elevated risk of child abuse (Fritze et al, 2008).…”
Section: Direct Psychological Impacts Of Global Climate Changementioning
confidence: 99%
“…lobal climate change is likely to have significant negative effects on mental health and well-being, effects that will be felt most by vulnerable populations and those with preexisting serious mental illness (Costello et al, 2009;Fritze, Blashki, Burke, & Wiseman, 2008;Page & Howard, 2010). Localized and/or immediate consequences, such as injury or stress resulting from more extreme weather events or degraded landscapes, may be perceived as direct, personal impacts of climate change (Kolbert, 2006).…”
mentioning
confidence: 99%
“…47 These effects will likely be greatest for communities already experiencing socioeconomic disadvantage. 48 …”
Section: Tertiary Effectsmentioning
confidence: 99%